2016
DOI: 10.1002/pssa.201533078
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and structural properties of Zn‐doped yttrium iron garnet nanoparticles

Abstract: Zn-doped YIG was prepared using the sol-gel method with TGA measurements showing the phase formation between 900 and 1000 8C. XRD analysis showed close to 1100 8C the formation of Franklinite phase, coexisting with the cubic YIG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…The resulting hysteresis curve in Figure 6 has a narrow gap and a saturation value above 0.5 Oe (equivalent to 0.00005 T) 7 . Based on this statement, the Y 3 Fe 5-x Ni x O 12 sample (x = 0.00, 0.02, 0.04, 0.06, 0.08) is included in soft magnetic materials (Pena-Garcia et al 38 ) Based on Figure 6, its magnetic characteristics can be analyzed using Magnetic Saturation (Ms), Magnetic remanence (Mr), and coercivity (Hc) presented in Table 3 which are obtained based on the approach of the hysteresis curve. The saturation magnetization (Ms) value for pure YIG nanoparticles was 23.684 emu/g.…”
Section: Magnetic Properties Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting hysteresis curve in Figure 6 has a narrow gap and a saturation value above 0.5 Oe (equivalent to 0.00005 T) 7 . Based on this statement, the Y 3 Fe 5-x Ni x O 12 sample (x = 0.00, 0.02, 0.04, 0.06, 0.08) is included in soft magnetic materials (Pena-Garcia et al 38 ) Based on Figure 6, its magnetic characteristics can be analyzed using Magnetic Saturation (Ms), Magnetic remanence (Mr), and coercivity (Hc) presented in Table 3 which are obtained based on the approach of the hysteresis curve. The saturation magnetization (Ms) value for pure YIG nanoparticles was 23.684 emu/g.…”
Section: Magnetic Properties Analysismentioning
confidence: 99%
“…Besides, Ni can also increase the value of Ms, such as the phenomenon at x = 0.06 due to the oxygen void caused by the presence of nickel. There is a strong spontaneous interaction between the oxygen vacancies and the magnetic ion in the octahedral lattice (Fe and Ni) that eliminates thermal effects and increases the sub-grid magnetic moment of the octahedral 38 . The very low Ms value at x = 0.08 with a value of 2.518 emu/g can be attributed to the spin canting mechanism where the substitution of Ni ions causes non-collinear spin changes, which lead to crystal lattice irregularities 7,25,38 .…”
Section: Magnetic Properties Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…12 Over the past several decades, several works on replacing YIG garnet with other metal ions have been reported; these studies revealed that the structural, morphological, | 813 CAO et Al. 16,17 Aldbea et al have shown that the Fe 3+ ions replaced by Al 3+ ions can improve the coercive field while decreasing the saturation magnetization and dielectric properties. 13,14 For instance, Chen F. et al have reported that the substitution of the Fe atoms with the Zr atoms at the 16a position can decrease the permeability and magnetic loss in the 1 to 100 MHz range.…”
Section: Introductionmentioning
confidence: 99%
“…15 Also, Peña-Garcia et al have found that Zn atoms replace the Fe atoms, increasing the crystal parameter with the concentration of dopant ions, and diminishing the magnetic moment. 16,17 Aldbea et al have shown that the Fe 3+ ions replaced by Al 3+ ions can improve the coercive field while decreasing the saturation magnetization and dielectric properties. 11 Guo et al confirmed that a replacement of the iron ions at the 16a position in YIG with an appropriate amount of the In 3+ ions significantly reduce the magnetic anisotropy and coercivity of YIG.…”
Section: Introductionmentioning
confidence: 99%